The Reality of China's Maritime Capability. Issue 3 (4th May 2018) - Murphy, Martin; Roberts, Peter
Abstract : It is the policy of the Chinese Communist Party that the country should become a great maritime power. In this article, Martin N Murphy and Peter Roberts provide an overview of what this means militarily, where China is laying down a challenge to the US and its regional neighbours, where it is falling short, and what this has to do with Europe.